Control of cell growth direction by direct fabrication of periodic micro- and submicrometer arrays on polymers - Langheinrich, Denise (2012)
In this work, we describe a laser-assisted microstructuring technique called Direct Laser Interference Patterning to produce topographical cues for tumor cells in a one-step process. Line-like patterns with spatial periods ranging from 500 nm to 10 μm are fabricated on polyimide (PI) films. The resulting structures exhibit a well-defined shape and quality even for patterns with small periodic distances. Subsequently, the behavior of mouse mammary adenocarcinoma cells over those structures is evaluated. The results show that cell growth is well aligned to the direction of the patterns (over 60% lying within 0° to 15°to either side of the surface lines) for all evaluated structure sizes. Moreover, cells grown on patterns with 500 nm spatial period are the most narrowly aligned (up to 80% found between 0°and 15°), showing the potential of the technique. The fabrication process of the PI patterns is supported by a mathematical model of the underlying photo-chemical ablation process.